Barkhausen Noise‐ and Eddy Current‐Based Measurements for Online Detection of Deformation‐Induced Martensite During Flow Forming of Metastable Austenitic Steel AISI 304L - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Engineering Reports)
ABSTRACT This paper deals with micromagnetic measurements for online detection of strain‐induced α′‐martensite during plastic deformation of metastable austenitic steel AISI 304L. The operating principles of the sensors are magnetic Barkhausen noise (MBN) and eddy currents (EC), which are suitable for detection of microstructure evolution due to formation of ferromagnetic phases. The focus of this study was put on the qualification of different micromagnetic techniques and different measurement systems under conditions similar to the real ones during production, which is crucial for implementation of a property‐controlled flow forming process. The investigation was carried out on tubular specimens produced by flow forming, which have different content of α′‐martensite. To characterize the sensitivity of the sensors, different contact conditions between sensors and workpieces were reproduced. MBN sensors are suitable for detecting amount of α′‐martensite, but the measurements are affected by the surface roughness. This entails that the calibration models for MBN sensors must take account of these effects. EC sensors show a closer match with the amount of α′‐martensite without having major affectation by other effects.

Optimizing Communication for Latency Sensitive HPC Applications on up to 48 FPGAs Using ACCL - Meyer, Marius; Kenter, Tobias; Petrica, Lucian; O’Brien, Kenneth; Blott, Michaela; Plessl, Christian (Lecture Notes in Computer Science)
Most FPGA boards in the HPC domain are well-suited for parallel scaling because of the direct integration of versatile and high-throughput network ports. However, the utilization of their network capabilities is often challenging and error-prone because the whole network stack and communication patterns have to be implemented and managed on the FPGAs. Also, this approach conceptually involves a trade-off between the performance potential of improved communication and the impact of resource consumption for communication infrastructure, since the utilized resources on the FPGAs could otherwise be used for computations. In this work, we investigate this trade-off, firstly, by using synthetic benchmarks to evaluate the different configuration options of the communication framework ACCL and their impact on communication latency and throughput. Finally, we use our findings to implement a shallow water simulation whose scalability heavily depends on low-latency communication. With a suitable configuration of ACCL, good scaling behavior can be shown to all 48 FPGAs installed in the system. Overall, the results show that the availability of inter-FPGA communication frameworks as well as the configurability of framework and network stack are crucial to achieve the best application performance with low latency communication.

A Computation of the Ninth Dedekind Number Using FPGA Supercomputing - Van Hirtum, Lennart; De Causmaecker, Patrick; Goemaere, Jens; Kenter, Tobias; Riebler, Heinrich; Lass, Michael; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems)
This manuscript makes the claim of having computed the 9th Dedekind number, D(9). This was done by accelerating the core operation of the process with an efficient FPGA design that outperforms an optimized 64-core CPU reference by 95x. The FPGA execution was parallelized on the Noctua 2 supercomputer at Paderborn University. The resulting value for D(9) is 286386577668298411128469151667598498812366. This value can be verified in two steps. We have made the data file containing the 490 M results available, each of which can be verified separately on CPU, and the whole file sums to our proposed value. The paper explains the mathematical approach in the first part, before putting the focus on a deep dive into the FPGA accelerator implementation followed by a performance analysis. The FPGA implementation was done in Register-Transfer Level using a dual-clock architecture and shows how we achieved an impressive FMax of 450 MHz on the targeted Stratix 10 GX 2,800 FPGAs. The total compute time used was 47,000 FPGA hours.

Optimisation and Evaluation of Breadth First Search with oneAPI/SYCL on Intel FPGAs: from Describing Algorithms to Describing Architectures - Olgu, Kaan; Kenter, Tobias; Nunez-Yanez, Jose; Mcintosh-Smith, Simon (Proceedings of the 12th International Workshop on OpenCL and SYCL)

Gewerblich-technische Lehrkräftebildung in Deutschland - Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats (Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2024)

Context-specific adaptation for head fakes in basketball: a study on player-specific fake-frequency schedules - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Giesen, Carina G.; Rothermund, Klaus; Weigelt, Matthias (Psychological Research)
In basketball, an attacking player often plays a pass to one side while looking to the other side. This head fake provokes a conflict in the observing opponent, as the processing of the head orientation interferes with the processing of the pass direction. Accordingly, responses to passes with head fakes are slower and result in more errors than responses to passes without head fakes (head-fake effect). The head-fake effect and structurally similar interference effects (e.g., Stroop effect) are modulated by the frequency of conflicting trials. Previous studies mostly applied a block-wise manipulation of proportion congruency. However, in basketball (and also in other team sports), where different individual opponents can be encountered, it might be important to take the individual frequency (e.g., 20% vs. 80%) of these opponents into account. Therefore, the present study investigates the possibility to quickly (i.e., on a trial-by-trial basis) reconfigure the response behavior to different proportions of incongruent trials, which are contingent on different basketball players. Results point out that participants indeed adapted to the fake-frequency of different basketball players, which could be the result of strategic adaptation processes. Multi-level analyses, however, indicate that a substantial portion of the player-specific adaptation to fake frequencies is accounted by episodic retrieval processes, suggesting that item-specific proportion congruency effects can be explained in terms of stimulus-response binding and retrieval: The head orientation (e.g., to the right) of a current stimulus retrieves the last episode with the same head orientation including the response that was part of this last episode. Thus, from a theoretical perspective, an attacking player would provoke the strongest detrimental effect on an opponent if s/he repeats the same head movement but changes the direction of the pass. Whether it is at all possible to strategically apply this recommendation in practice needs still to be answered.

Forecasting economic growth by combining local linear and standard approaches - Fritz, Marlon; Forstinger, Sarah; Feng, Yuanhua; Gries, Thomas (Journal of Applied Statistics)

Energy and sustainability: a balanced energy transition strategy - Kolosok, Svitlana; Myroshnychenko, Iuliia; Gries, Thomas (The Elgar Companion to Energy and Sustainability)

Trendbericht Organische Chemie 2024 - Breugst, Martin; Andexer, Jennifer; Barra, Lena; Beil, Sebastian B.; Breinbauer, Rolf; Burkhardt, Immo; Dumele, Oliver; Ernst, Martin; Gellrich, Urs; Germer, Philipp; Giese, Michael; Huy, Peter; et al. (Nachrichten aus der Chemie)
Abstract Unter anderem das hat die Organik im letzten Jahr bewegt: milde Oxidation mit Elektrochemie, Oxidation zu enantiomerenreinen Sulfonylverbindungen, Flüssigkristallphasen erkennen mit maschinellem Lernen, CO 2 reagiert zu Succinat und Carbamaten, eine Alternative zu Bisphenol A, Subporphyrine, photoschaltbare Spinmaterialien, photochemische Thiophen‐Ringerweiterung, und Peptide werden mit Bor versehen und cyclisiert. Die Zusammenstellung des Trendberichts koordiniert hat Martin Breugst, Universität Chemnitz.

Design, isolation, synthesis, and mechanistic insight of flavonoids isolated from Beilschmiedia obscura, as potential α-glucosidase inhibitors - Nyemeck, Suzanne L.; Eyong, Kenneth O.; Bidingha, Ronald; Kamdem, Michael HK.; Ndinteh, Derek T.; Odumosu, Patricia O.; Folefoc, Gabriel N.; Bilanda, Danielle C.; Egbe, Andrew E.; Werner, Thomas; Bekono, Boris D.; Ntie-Kang, Fidele (Phytochemistry Letters)
Keywords: T4

Tuneable reduction of CO2 – organocatalyzed selective formylation and methylation of amines - Ren, Changyue; Terazzi, Constanza; Werner, Thomas (Green Chemistry)
The selective N -formylation and N -methylation of amines with carbon dioxide (CO 2 ) catalyzed by methyltriphenylphosphonium methylcarbonate and tuned by polymethylhydrosiloxane or trimethoxysilane as reducing agents is reported.
Keywords: T1; T2; CSSD

Phosphonium-Salt-Catalyzed N-Methylation and N-Formylation of Amines with CO2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: T1; T2; CSSD

Synthesis of Trisubstituted Furans from Activated Alkenes by P(III)/P(V) Redox Cycling Catalysis - Tönjes, Jan; Medvarić, Viktorija; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: T2; CSSD

Unveiling the Impact of Flexible Work on Employer Attractiveness: Examining the Role of Work Experience - Radermacher, Katharina; Horsthemke, Johanna; Täuber, Mona (Herbstworkshop WK Pers)

Influence of liquid metal embrittlement on the failure behavior of dissimilar spot welds with advanced high-strength steel: A component study - Yang, Keke; Sowada, Matthias; Olfert, Viktoria; Seitz, Georg; Schreiber, Vincent; Heitmann, Marcel; Hein, David; Biegler, Max; Jüttner, Sven; Rethmeier, Michael; Meschut, Gerson (Journal of Materials Research and Technology)

Importance of cultural change in Systems Engineering Transformation: A model for cultural assessment - Graessler, Iris; Grewe, Benedikt (AHFE International)
Systems Engineering is becoming increasingly important in the engineering of complex technical systems. Its introduction is forcing companies to undertake major transformation initiatives. As established change management approaches show, the corporate culture is an important key criterion for success of transformation. Therefore, when introducing Systems Engineering into an organization, transformation initiatives must be tailored to an existing corporate culture or the corporate culture itself must be changed in order to enable Systems Engineering. In literature and in industrial practice, different approaches for assessment of corporate culture exist. Within this research, a systematic literature review on methods and models for corporate culture assessment is conducted. Core elements are collected and combined with the fundamentals and success factors of Systems Engineering to develop a model for corporate culture assessment. The developed model is applied to the industrial practice of an ongoing Systems Engineering transformation of a large car manufacturer. The results of the assessment are compared with the emerging project challenges. Based on this model and its supporting tool and templates, organizations and transformation leaders are enabled to rapidly obtain an orientation of hindering or supporting currently established cultural aspects with regard to Systems Engineering transformation and to provide a decision basis for further measures.

Eine empirische Untersuchung von Business-to-Business Online-Bewertung - Rode, Christoph

SootUp: A Redesign of the Soot Static Analysis Framework - Karakaya, Kadiray; Schott, Stefan; Klauke, Jonas; Bodden, Eric; Schmidt, Markus; Luo, Linghui; He, Dongjie (Tools and Algorithms for the Construction and Analysis of Systems)
Abstract Since its inception two decades ago, Soot has become one of the most widely used open-source static analysis frameworks. Over time it has been extended with the contributions of countless researchers. Yet, at the same time, the requirements for Soot have changed over the years and become increasingly at odds with some of the major design decisions that underlie it. In this work, we thus present SootUp , a complete reimplementation of Soot that seeks to fulfill these requirements with a novel design, while at the same time keeping elements that Soot users have grown accustomed to.

Java Bytecode Normalization for Code Similarity Analysis - Schott, Stefan; Ponta, Serena Elisa; Fischer, Wolfram; Klauke, Jonas; Bodden, Eric (38th European Conference on Object-Oriented Programming (ECOOP 2024))

Compilation of Commit Changes Within Java Source Code Repositories - Schott, Stefan; Fischer, Wolfram; Ponta, Serena Elisa; Klauke, Jonas; Bodden, Eric (2024 IEEE International Conference on Software Maintenance and Evolution (ICSME))